2020
DOI: 10.1080/07391102.2020.1842806
|View full text |Cite
|
Sign up to set email alerts
|

Identification of natural inhibitors against Mpro of SARS-CoV-2 by molecular docking, molecular dynamics simulation, and MM/PBSA methods

Abstract: The recent outbreak of SARS-CoV-2 disease, also known as COVID-19, has emerged as a pandemic. The unavailability of specific therapeutic drugs and vaccines urgently demands sincere efforts for drug discovery against COVID-19. The main protease (Mpro) of SARS-CoV-2 is a critical drug target as it plays an essential role in virus replication. Therefore for the identification of potential inhibitors of SARS-CoV-2 Mpro, we applied a structure-based virtual screening approach followed by molecular dynamics (MD) stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 26 publications
1
18
0
Order By: Relevance
“…The interactions are highly favoured by Van der Waal interactions and electrostatic interactions together. Polar solvation energy individually dominates the binding energy [ 56 , 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…The interactions are highly favoured by Van der Waal interactions and electrostatic interactions together. Polar solvation energy individually dominates the binding energy [ 56 , 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…There are many reports on the use of molecular docking/in-silico studies to investigate the effectiveness of different types of drugs/molecules to inhibit the replication of the SARS-COV-2 main protease (Mpro). The effective binding of different phytochemicals, biomolecules, drugs and drug-like molecules have been examined and found that majority of the molecules investigated above does not bind to all the active sites effectively (Abu-Saleh et al 2020 ; Amin et al 2020 ; Basu et al 2020 ; Cavasotto and Filippo 2020 ; Choudhary et al 2020a , b ; Lokhande et al 2020 ; Peele et al 2020 ; Sharma et al 2020 ; Tallei et al 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…(Abu-Saleh et al 2020;Amin et al 2020;Basu et al 2020; Cavasotto and Filippo 2020; Choudhary et al 2020a, b;Lokhande et al 2020;Peele et al 2020;Sharma et al 2020;Tallei et al 2020). …”
mentioning
confidence: 99%
“…The oxo group at the 14th position and the carbonyl oxygen of carboxylic acid at the second position of icosahydropicene-2-carboxylic acid core nucleus of GA exhibited conventional hydrogen bond interactions with the amino group of GLN189 (3.01 and 2.19 Å, respectively). Further, hydrophobic alkyl interactions were observed between the icosahydropicene-2-carboxylic acid core nucleus methyl groups of GA with CYS145 ( Several literature evidences are implicating that SARS-CoV-2 M pro could be used for screening purposes to predict the binding affinity of the approved drugs, natural inhibitors, and those in clinical trials [5,[42][43][44]. The binding stability of an α-ketoamide inhibitor O6K or 13b as reference control inside the SARS-CoV-2 M pro was carried out to assess affinity score and determine theoretically the possible and probable active site residues involved in the formation of complex, which was found consistent with our observation [44][45][46][47].…”
Section: Binding Interactions Of Potential Antiviral Agents At the Acmentioning
confidence: 99%